Animal Behaviour - Time-Life Books (Time Life Books : Hong Kong, 1994)
This volume explores the fascinating behavior of animals in a colorful, engaging format. Organized around key questions, it covers: Communication methods (sounds, visual signals) Social organization within species (packs, colonies, hierarchies) Feeding, hunting, and survival strategies Reproduction, parental care, migration and instincts Illustrated with real-life photos, diagrams, and captions to appeal to young readers and general audiences.
Keywords: Animal behaviour